Intersexualidade e corpos intersexo em livros didáticos de Biologia (PNLD 2012-2018) - Silva, Luciana Aparecida Siqueira (2022)
This thesis was produced within the scope of the Science and Mathematics Education line of the Graduate Program in Education at the Federal University of Uberlândia. To delineate the research problem, we consider that thinking about school Biology involves thinking about the regimes of truth that produce Biology as a science, and these, based on biomedical assumptions, carry and disseminate a set of laws, rules and statements of truth about the bodies and the sexes, often not surprised by their professionals. We question what and how Biology textbooks put into operation knowledge about intersex bodies and what approximations they make with the defenses of the intersex movement in Brazil; we problematize the teachings and knowledge about the intersex body and intersexuality present in them and the possible resistances to the power-knowledge networks that permeate these bodies. We draw a diagram of the texts and images about intersex bodies present in the three collections of Biology textbooks approved by the PNLD 2012, 2015 and 2018, most adopted by Brazilian schools; we describe the constitutive elements of the mechanisms of truth disseminated by/in books on the notions of the intersex body and intersexuality; and, we analyze the possibilities of approximations between knowledges in the approach of intersex bodies in these books. We take as reference Feminist Studies, Gender Studies and current intersexuality studies, and the textbook as a document, device, cultural production and as a commodity. We chose authors from the critical and post-critical fields of Education and Human Sciences in general, and we undertook a descriptive-documentary analysis assuming that the Biology textbook carries the traces of the production of the field of biological knowledge, of culture, of the field pedagogical, of the time and society of its production, through the various assemblies and reassembly of knowledge-powers. We also map the traces of knowledge about intersex bodies and intersexuality, their continuities and discontinuities. The three collections, when compared to each other, present similarities in approach, with variations related to the availability of complementary texts and guidelines for deepening the theme or work to be carried out by the teacher. Considering the textbook as a device, it is possible to affirm that it reiterates sexual and gender binarism. Teachings about the intersex body and intersexuality are supported by biomedical knowledge, far from the productions of the social movement and the most recent academic production, both in the biomedical sciences and the human sciences. They make invisible/erase, through language, the use of the terms intersex and intersexuality; put differences in sexual development in place of disease; prescribe medical and family practices, attaching to these the need for medical interventions to standardize bodies to sexual binarism, heterosexuality and the reproductive pattern via sex. The production of intersexuality is accompanied by a biopolitical investment that manages lives also through the control and disciplining of bodies. School Biology has the potential to overcome the thinking that creates the notion of normality of bodies, genders and (inter)sexualities disconnected from social, civil, societal and subjective rights.